A WEB SERVICE APLIKASI FEEDER DENGAN LIBRARY NUSOAP UNIVERSITAS MUHAMMADIYAH BENGKULU - Marhalim, Marhalim; Juhardi, Ujang; Khairullah, Khairullah (UNIVED Press, 2021)
Research carried out at Muhammadiyah University of Bengkulu is developing a web service with the nusoap library which can interoperate with feeder applications for integrating academic report data. By developing web services, academic reporting can be made easier and the development of existing academic information systems easier. The web service that has been developed by researchers can currently do several things, namely the web service logs into the feeder, lists the tables in the feeder, views each table with the GetRecordSet request, views GetDictionary, GetRecord, imports new student data and KRS with the InsertRecordSet request and Update student grades with the UpdateRecordSet request.